Biological science (Pearson, 2017)
With the Sixth Edition, content has been streamlined with an emphasis on core concepts and core competencies from the Vision and Change in Undergraduate Biology Education report. The text’s unique BioSkills section is now placed after Chapter 1 to help students develop key skills needed to become a scientist, new “Making Models” boxes guide learners in interpreting and creating models, and new “Put It all Together” case studies conclude each chapter and help students see connections between chapter content and current, real-world research questions. New, engaging content includes updated coverage of global climate change, advances in genetic editing, and recent insights into the evolution of land plants. Strong media Integration supports book features with MasteringBiology activities, Learning Catalytics™, and new whiteboard videos that guide students in completing “Making Models” assignments.